Temple Theology in the New Testament: Relocation and replacement toward the Temple of the Holy Spirit - Gil Soldevilla, Samuel (2016)
This essay is a practical and fundamentally biblical reflection on God's presence in relation to the human being, which we identified and divided as a methodological approach on five particular moments in history. We focus on the texts of the New Testament because from these is confirme and produces the relocation and replacement of the Temple Theology. Finally, the God's houses, built by humans, surrender to the meaning of Christ as Redeemer in each person and in his Church through the Holy Spirit, making us the God's living temples